The Power of Outliers in Research: What actually Works, and Does it Matter? (Pravaha, 2024)
Outliers have an important and diverse role in the social sciences, particularly when seen via a statistical lens. While outliers are frequently perceived as abnormalities or departures from the norm, they can contribute critical insights and improve our knowledge of social processes. Outliers, sometimes referred to as anomalies in datasets, play an important role in the development of research. While typically regarded as a threat to statistical integrity, their existence can produce surprising insights and breakthrough findings when managed correctly. This article investigates the varied nature of outliers, their influence on research methodology, and their contribution to significant scientific advances. We examine how to successfully discover, analyze, and use outliers, balancing their potential for innovation against the risk of drawing incorrect conclusions.